Enabling Solar Fuels Technology With High Throughput Experimentation. Issue 1654 (7th January 2014) - Gregoire, J. M.; Haber, J. A.; Mitrovic, S.; Xiang, C.; Suram, S.; Newhouse, P. F.; Soedarmadji, E.; Marcin, M.; Kan, K.; Guevarra, D.; Jones, R.; Becerra, N.; et al.
ABSTRACT: The High Throughput Experimentation (HTE) project of the Joint Center for Artificial Photosynthesis (JCAP, http://solarfuelshub.org/ ) performs accelerated discovery of new earth-abundant photoabsorbers and electrocatalysts. Through collaboration within the DOE solar fuels hub and with the broader research community, the new materials will be utilized in devices that efficiently convert solar energy, water and carbon dioxide into transportation fuels. JCAP-HTE builds high-throughput pipelines for the synthesis, screening and characterization of photoelectrochemical materials. In addition to a summary of these pipelines, we will describe several new screening instruments for high throughput (photo-)electrochemical measurements. These instruments are not only optimized for screening against solar fuels requirements, but also provide new tools for the broader combinatorial materials science community. We will also describe the high throughput discovery, follow-on verification, and device implementation of a new quaternary metal oxide catalyst. This rapid technology development from discovery to device implementation is a hallmark of the multi-faceted JCAP research effort.